Production of H2-Rich Syngas From Lignocellulosic Biomass Using Microwave-Assisted Pyrolysis Coupled With Activated Carbon Enabled Reforming - Shi, Kaiqi; Yan, Jiefeng; Menéndez, J. Angel; Luo, Xiang; Yang, Gang; Chen, Yipei; Lester, Edward; Wu, Tao (Frontiers in Chemistry, 2020)
This study focuses on the use of a microwave reactor that combines biomass pyrolysis, at mild temperature, with catalytic reforming of the pyrolytic gas, using activated carbon, for generating hydrogen-rich synthesis gas. The traditional pyrolysis of biomass coupled with the reforming of its pyrolytic yields were also conducted using an electrically heated reactor. The bio-oil attained from conventional pyrolysis was higher in comparison to the yield from microwave pyrolysis. The reforming of the pyrolytic yields led to reductions in bio-oil yield to <3.0 wt%, with a simultaneous increase in gaseous yields. An increase in the syngas and H2 selectivity was discovered with the reforming process such that the use of microwave pyrolysis with activated carbon reforming produced 85 vol% synthesis gas fraction containing 55 vol% H2 in comparison to the 74 vol% syngas fraction with 30 vol% H2 obtained without the reforming. Cracking reactions were improved with microwave heating, while deoxidation and dehydrogenation reactions were enhanced by activated carbon, which creates a reduced environment. Consequently, these reactions generated H2-rich syngas formation. The approach implemented in this study revealed higher H2, syngas yield and that the overall LHV of products has huge potential in the transformation of biomass into high-value synthesis gas.